2015
DOI: 10.1002/pc.23445
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and use as emissive layer of white organic light emitting diodes of the highly isotactic poly(N‐pentenyl‐carbazole)

Abstract: The synthesis and the microstructural characterization of isotactic poly (N‐pentenyl‐carbazole) (i‐PPK) are reported. The achieved polymer is semicrystalline, the melting temperature is 138°C. i‐PPK Fourier transform infrared spectroscopy (FTIR) spectrum and X‐ray diffraction pattern are compared with those of polyvinylcarbazole. The observed differences are tentatively associated to higher flexibility of the i‐PPK chains due to the alkylene group connecting the carbazole group to the main chain. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 25 publications
9
53
0
Order By: Relevance
“…Consistently with these observations, the fluorescence spectra of diluted solutions of our synthesized stereoregular polymers collected at room temperature do not exhibit excimer emission, but only the monomer fluorescence is observed. Conversely, we found that all our synthesized stereoregular polymers in the solid state as thin films, show both sandwich‐like and “partially overlapped” excimer emissions . These results were explained assuming that polymer chain conformational freedom in solution prevents excimer formation, while on the other side, in the solid state and at temperatures lower than glass transition temperature ( T g ), a reduced conformational freedom allows the excimer formation .…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Consistently with these observations, the fluorescence spectra of diluted solutions of our synthesized stereoregular polymers collected at room temperature do not exhibit excimer emission, but only the monomer fluorescence is observed. Conversely, we found that all our synthesized stereoregular polymers in the solid state as thin films, show both sandwich‐like and “partially overlapped” excimer emissions . These results were explained assuming that polymer chain conformational freedom in solution prevents excimer formation, while on the other side, in the solid state and at temperatures lower than glass transition temperature ( T g ), a reduced conformational freedom allows the excimer formation .…”
Section: Introductionmentioning
confidence: 77%
“…Starting from PVK, several polymers with novel molecular structures have been prepared . It is well known that PVK optical properties are related to the peculiar structural feature of the polymer giving rise to two spectrally distinct excimer fluorescences .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19) by a homogeneous Ziegler-Natta catalytic system of rac-[(CH 3 ) 2 Si(indenyl) 2 ]ZrCl 2 and methylallumoxane (MAO) in toluene at 20°C. 63 Interestingly, i-PPK film showed a broad emission spectrum from 350 nm to 600 nm, probably due to the presence of singlet and triplet excimers similar to the case of poly(N-vinylcarbazole). 56 Given the broad emission, i-PPK was an ideal candidate for white PLED device [ITO/PEDOT:PSS (40 nm)/i-PPK (70 nm)/ BCP (10 nm)/Alq 3 (10 nm)/Ca (30 nm)/Al (70 nm)] which gave a broad electroluminescence spectrum covering from 400 nm to 800 nm with three peaks at 420 nm, 520 nm, and 620 nm.…”
Section: Fluorescent Polymersmentioning
confidence: 99%
“…Indeed, the PLQYs of non-conjugated fluorescent polymers are competitive (up to 61% in THF) 61 and the surface roughness seems to not depend on the nature of the polymer backbone (R a < 1 nm). 26,63 Considering the key difference between fluorescent polymers and phosphorescent/TADF analogues is the utilization of triplet excitons for emission in the latter two types of materials, one might wonder if the nature of the polymer backbone affected the exciton utilization efficiency (g S ), hence, resulting in the remarkably different PLED efficiencies demonstrated by non-conjugated and conjugated fluorescent polymers. The internal quantum efficiency (IQE) of PLED is strongly related to g S according to the following expression 138 :…”
Section: Conjugated Versus Non-conjugated Polymers: Pled Performancesmentioning
confidence: 99%